Diversity, carbon stock and economic value of the mangrove ecosystem in Wakatobi Biosphere Reserve, Indonesia - ABDUL MANAN; LA BACO SUDIA; UMAR ODE HASANI; SURYA CIPTA RAMADHAN KETE; LA GANDRI; ASRAMID YASIN; AGUSRINAL AGUSRINAL; ISABELA ISABELA (Society for Indonesian Biodiversity, 2025)
Abstract. Manan A, Sudia LB, Hasani UO, Kete SCR, Gandri L, Yasin A, Agusrinal, Isabela. 2025. Diversity, carbon stock and economic value of the mangrove ecosystem in Wakatobi Biosphere Reserve, Indonesia. Biodiversitas 26: 1095-1104. Mangrove ecosystems significantly contribute to climate change mitigation through the absorption and storage of carbon. This research evaluates the diversity, carbon stock, and economic valuation of mangrove ecosystems within the Wakatobi Biosphere Reserve. Data collection occurred at 11 stations distributed among four primary islands: Kaledupa, Wangi-Wangi, Tomia, and Binongko. Diameter at Breast Height (DBH) measurements were utilized to estimate biomass and carbon storage, employing species-specific allometric equations. Economic valuation utilized carbon trading data from the Indonesia Stock Exchange (IDX Carbon) as of 3 January 2025, alongside the Social Cost of Carbon (SCC) and Voluntary Market (VM) prices. The mangrove ecosystem of the Wakatobi Biosphere Reserve covers an area of 10,994 hectares and is in excellent ecological condition. The Shannon-Wiener Diversity Index values for tree and pole strata demonstrate moderate diversity (1-3), with Kaledupa and Binongko classified as moderate, whereas Wangi-Wangi and Tomia are categorized as low (<1). The evenness score indicates a high classification for tree strata (>0,6), with the exception of Wangi-Wangi, which is classified as medium (0,4-0,6). Wangi-Wangi Island is classified as low for splinter strata (<0,4), whereas Tomia, Kaledupa, and Binongko Islands are classified as medium. The composition of mangrove species differed across islands, with Sonneratia alba, Rhizophora mucronata, Bruguiera gymnorrhiza, and Ceriops tagal identified as the most prevalent species and significant contributors to carbon sequestration. The total carbon stock was estimated at 329,82.06 tons, with Kaledupa Island exhibiting the highest stock at 317,226.51 tons, while Binongko Island recorded the lowest at 2,053.8 tons. The economic valuation of carbon storage indicates significant potential: IDR 18,763,377,420 or USD 1,159,307 (IDX Carbon), IDR 266,390,582,055 or USD 16,459,103 (SCC), and IDR 43,155,274,293 or USD 2,666,375 (VM), underscoring the financial importance of mangrove conservation. This signifies a potential for revenue generation in the Wakatobi region, offering a hopeful prospect for the future. This study highlights the ecological and economic significance of mangroves and establishes a basis for sustainable conservation and management strategies aimed at improving the resilience of the Wakatobi Biosphere Reserve.